Simultaneous Generation of Multi-Channel Broadband Chaotic Signals Based on Two Unidirectionally Coupled WRC-FPLDs - Chun-Xia Hu; Guang-Qiong Xia; Zai-Fu Jiang; Dian-Zuo Yue; Wen-Yan Yang; Gong-Ru Lin; Zheng-Mao Wu (IEEE Photonics Journal, 2020)
We propose and demonstrate experimentally a scheme for simultaneously generating multi-channel broadband chaotic signals based on two unidirectionally coupled weak-resonant-cavity Fabry-Perot laser diodes (WRC-FPLDs) with almost the same mode interval, where one WRC-FPLD is utilized as master WRC-FPLD (M-WRC-FPLD) and the other is used as slave WRC-FPLD (S-WRC-FPLD). Under the optical injection from the M-WRC-FPLD with suitable injection parameters, multiple longitudinal modes of the S-WRC-FPLD can be simultaneously driven into chaotic states, which can provide multi-channel chaotic signals. Via a tunable optical filter, we inspect the performances of 9-channel chaotic signals, the results show that the chaotic bandwidths are within the range of 8∼15 GHz for all the 9-channel chaotic signals. Furthermore, the influences of the injection power and frequency detuning on the performances of the chaotic output from one of the channels are also analyzed.